(3Z)-3-[(Z)-2-(2-Oxoindolin-3-ylidene)hydrazin-1-ylidene]indolin-2-one 0.17-hydrate - Yong-Hong Liu (Acta Crystallographica Section E, 2014)
In the title compound, C16H10N4O2·0.17H2O, prepared by the one-step condensation reaction of isatin with hydrazine hydrate under microwave irradiation, the complete organic molecule is generated by crystallographic inversion symmetry and therefore exists in an S-trans conformation. In the crystal, molecules are linked by N—H...O hydrogen bonds, generating a three-dimensional framework with [001] channels, which are occupied by the disordered water molecules.